EXPLORING ORGANIZATIONAL CAPACITY STRENGTHENING FACTORS INFLUENCING THE USE OF COMMUNICATION FOR DEVELOPMENT TECHNIQUES FOR ENHANCEMENT OF PRIMARY HEALTH CARE SERVICES ADMINISTRATION IN NIGERIA - Ibrahim, Adamkolo Mohammed; Gambo, Danjuma (PEOPLE: International Journal of Social Sciences, 2019)
The impacts of organizational capacity-strengthening support provided by local non-governmental organizations toward the utilization of communication for development techniques (advocacy and behavior change communication) for the improvement of primary health care services administration in the North-eastern Nigerian state of Yobe were explored. Using the organizational capacity assessment tool model and critical discourse analysis, the responses of five key management personnel of Yobe State Primary Health Care Management Board were analyzed. Organizational capacity strengthening in respect of organizational governance, coordination and partnerships, organizational planning, human resource development and management board dimensions appeared to have salient influences on the utilization of communication for development techniques in primary health care services administration with budgeting and financing dimensions having weaker influences. Perceived sustainability crisis and government political commitment appeared to play a moderating role.